denae24
contestada

Given that f(x) = x2 – 10x + 16 and g(x) = x – 8, find (f – g)(x) and
express the result in standard form.

Respuesta :

Answer:

[tex](f-g)(x)=x^2-11x+24[/tex]

Step-by-step explanation:

So we know that:

[tex]f(x)=x^2-10x+16\text{ and } g(x)=x-8[/tex]

And we want to find (f-g)(x).

This is the same as:

[tex](f-g)(x)=f(x)-g(x)[/tex]

Substitute:

[tex]=(x^2-10x+16)-(x-8)[/tex]

Distribute the right:

[tex]=(x^2-10x+16)-x+8[/tex]

Combine like terms:

[tex]=x^2-11x+24[/tex]

And we're done!

ACCESS MORE